Heterogeneity of patients receiving artificial nutrition in Japanese psychiatric hospitals: a cross‐sectional study. Issue 6 (12th January 2016) - Hirao, Akihiko; Abe, Keiichi; Takayama, Keiko; Kondo, Keiko; Yokota, Osamu; Sato, Yoshiki; Norikiyo, Taizo; Sato, Soichiro; Nakashima, Tadao; Hayashi, Hideki; Nakata, Kenji; Asaba, Hiroyuki; et al.
Abstract: Aim: Artificial nutrition, including tube feeding, continues to be given to dementia patients in numerous geriatric facilities in Japan. However, the clinical characteristics of patients receiving artificial nutrition have not been fully investigated. Therefore, we tried to evaluate the clinical features of those patients in this study. Methods: Various clinical characteristics of all inpatients at 18 of 20 psychiatric hospitals in Okayama Prefecture, Japan, with a percutaneous endoscopic gastrostomy tube, nasogastric tube, or total parenteral nutrition were evaluated. Results: Two hundred twenty‐one patients (5.4% of all inpatients) had been receiving artificial nutrition for more than 1 month, and 187 (130 women, 57 men; 84.6% of 221 patients) were fully investigated. The mean age was 78.3 years old, and the mean duration of artificial nutrition was 29.8 months. Eighty‐four patients (44.7% of 187 patients) were receiving artificial nutrition for more than 2 years. Patients with Alzheimer's disease ( n = 78) formed the biggest group, schizophrenia ( n = 37) the second, and vascular dementia ( n = 26) the third. Conclusion: About one‐fifth of the subjects receiving artificial nutrition were in a vegetative state. More than a few patients with mental disorders, including schizophrenia, also received long‐term artificial nutrition. We should pay more attention to chronic dysphasia syndrome in mental disorders.